2018
DOI: 10.1590/0102-311x00029517
|View full text |Cite
|
Sign up to set email alerts
|

Focusing neighborhood context and self-rated health in the Pró-Saúde Study

Abstract: The influence of neighborhood characteristics on self-rated health has been little studied. A multilevel approach using hierarchical models was applied to analyze the relationship between the socioeconomic characteristics in 621 neighborhoods (level 2) in the city of Rio de Janeiro, Brazil, and the self-rated health of 3,054 university employees (level 1) from the baseline of the Pró-Saúde Study. Neighborhoods were created using the SKATER algorithm (Spatial ‘K’luster Analysis by Tree Edge Removal) to cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
2
11
1
2
Order By: Relevance
“…Contrary to the extensive descriptions in the literature, 2 - 4 age was not associated with poor self-rated health among teachers. Older teachers had a slightly higher prevalence of poor self-rated health, but this was insufficient to achieve statistical significance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the extensive descriptions in the literature, 2 - 4 age was not associated with poor self-rated health among teachers. Older teachers had a slightly higher prevalence of poor self-rated health, but this was insufficient to achieve statistical significance.…”
Section: Discussioncontrasting
confidence: 99%
“…Another aspect is that in the present study poor self-perceived health was made up of the group of teachers who answered that their health was “poor” or “regular”, as commonly occurs in the literature. 2 - 4 Since two of the earlier studies used the same answer structure, 17 , 19 it was possible to compare the results for the same construct. However, in the EDUCATEL study, 18 self-rated health was assessed with different answer options and three categories were clustered to categorize poor and regular answers (very poor, poor, regular).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Association observed for social disorder in the unadjusted model disappeared when individual-level covariates were adjusted for. Other studies have found that quality of services, mobility, public facilities, safety from traffic, violence, presence of parks, street noise, income, overcrowding, and the water, sewage network, electricity, and garbage collection services were related to health status [12,15,31,[41][42][43]. It is possible that many of these elements are better captured in the physical disorder scale that we used.…”
Section: Discussionmentioning
confidence: 99%
“…Urban environment features may affect health through a multiplicity of processes including influencing health-related behaviors through features such as walkability, the location of parks and green spaces, and access to and advertising for different types of foods. Other•mechanisms may include community stressors such as violence or lack of safety and the availability of social connections and social support mechanisms [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%